Modern Trends in Constructive Function Theory. - Simanek, Brian Z. (Contemporary Mathematics., 2016)
This volume contains the proceedings of the conference Constructive Functions 2014, held from May 26-30, 2014, at Vanderbilt University, Nashville, TN, in honor of Ed Saff's 70th birthday. The papers in this volume contain results on polynomial approximation, rational approximation, Log-optimal configurations on the sphere, random continued fractions, ratio asymptotics for multiple orthogonal polynomials, the bivariate trigonometric moment problem, minimal Riesz energy, random polynomials, Padé and Hermite-Padé approximation, orthogonal expansions, hyperbolic differential equations, Bergman po.